Model Pembelajaran Berbasis Masalah Terhadap Kemampuan Berpikir Kritis Siswa Mata Pelajaran Ekonomi - Sopia Lacuba; F.Y. Khosmas; Syamsuri Syamsuri; Husni Syahrudin (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This research study aims to determine: 1) The implementation of student problem-based learning in economics class X Madrasah Aliyah Negeri 1 Pontianak. 2) the ability to think critically of students in Economics in class X Madrasah Aliyah Negeri 1 Pontianak. 3) The effect of problem-based learning model on students' critical thinking in Economics class X MAN 1 Pontianak. This study uses quantitative methods to collect information through polls or questionnaires, documentation. The results of this paper show 1) The implementation of student problem-based learning in Economics class X MAN 1 Pontianak with a percentage of 81.48% with a very good category. 2) The ability to think critically of students in Economics in class X MAN 1 Pontianak with a percentage of 80.48% with a very high category. 3) The effect of the problem-based learning model on the critical thinking skills of students of class X economics at MAN 1 Pontianak, namely there is an influence of 43%, while the remaining 57% is thought to be influenced by other variables that the researchers did not examine further.